233k views
5 votes
I’ve been trying to figure out how to solve this and was wondering how to do this correctly!

I’ve been trying to figure out how to solve this and was wondering how to do this-example-1
User Anil D
by
5.3k points

1 Answer

5 votes

SOLUTION

To solve this we will use the form for exponential growth to determine the formula to use.

Exponential growth has the form


\begin{gathered} P=P_0e^(rt) \\ P=\text{population after timer t} \\ P_0=\text{ initial population growth } \\ r=\text{ percent growth rate} \end{gathered}

Now the frogs tripple in population after 9 days. Initially they were 21. So in 9 days they become


21*3=63\text{ frogs }

Applying the formula, we have


\begin{gathered} P=P_0e^(rt) \\ 63=21e^(9r) \\ 3=e^(9r) \\ \text{taking ln of both sides } \\ \ln 3=\ln e^(9r) \\ \ln 3=9r \\ r=(\ln3)/(9) \end{gathered}

The time for the frogs to get to 290 becomes


undefined

User Xiao Hanyu
by
5.3k points